Penerapan Konsep Arsitektur Hijau pada Perancangan Kembali Terminal Bus Tipe A Banda Aceh - Maudy Noviyanti Nada; Husnus Sawab; Riza Aulia Putra (Universitas Syiah Kuala, 2022)
The terminal as a public facility that continues to operate actively throughout the day, of course, consumes large amounts of energy every day. But unfortunately not all energy on earth can be renewed. Therefore, preventive measures are needed so that the energy on earth does not run out. The choice of the Green Architecture theme in the redesign of the Batoh bus terminal is expected to reduce the use of excess energy at the terminal. The application of the Green Architecture theme is carried out on each item in the redesign of the Batoh bus terminal, both the arrangement of the outer space, the inner space, to the selection of the right material and according to the design objectives. Some examples of the application of Green Architecture in this design are the use of glass with a secondary skin as a wall to facilitate the entry of light into the building so as to reduce the use of artificial light during the day while maintaining the temperature in the room so it is not hot Use of photovoltaics as an alternative energy source; As well as processing gray water as a source of additional water and others. From this concept, it is hoped that it can create a terminal that is more environmentally friendly so that the current energy can continue to be used in the future. Terminal sebagai fasilitas publik yang terus beroperasi secara aktif sepanjang hari tentu saja mengkonsumsi energi dalam jumlah besar setiap harinya. Namun sayangnya tidak semua energi di bumi dapat diperbarui. Maka dari itu, langkah pencegahan dibutuhkan agar energi di bumi tidak menipis. Pemilihan tema Green Architecture dalam perancangan kembali terminal bus batoh diharap dapat mengurangi penggunaan energi yang berlebih pada terminal. Penerapan Tema Green Architecture dilakukan pada setiap item dalam perancangan kembali terminal bus batoh, baik penataan ruang luar, ruang dalam, hingga pemilihan material yang tepat dan sesuai dengan tujuan perancangan. Beberapa contoh penerapan Green Architecture dalam perancangan ini ialah, penggunaan kaca low e-glass dan secondary skin sebagai dinding untuk memudahkan masuknya cahaya kedalam bangunan sehingga mengurangi penggunaan cahaya buatan pada siang hari namun tetap menjaga suhu dalam ruangan agar tidak panas; Penggunaan photovoltaic sebagai sumber energi alternatif; serta pengolahan gray water sebagai sumber air tambahan dan lainnya. Dari konsep ini diharapkan dapat menciptakan terminal yang lebih ramah lingkungan sehingga energi yang ada sekarang dapat terus dipergunakan hingga masa yang akan datang.